Post COVID-19: New Era for Higher Education Systems - Kayyali, Mustafa (International Journal of Applied Science and Engineering (India), 2020)
On November 17, 2019, according to several sources, the first case of COVID-19 appeared in Wuhan, China, for a 55-year-old man. In addition to that, evolutionary estimates in genetic studies conducted in the early months of 2020 indicated that the Severe Acute Respiratory Syndrome (SARS) Virus most likely transfered to humans in the period between October 6th, 2019 and December 11th, 2019. The reason that led to the rapid spread of this epidemic is that its symptoms may not appear on the infected person in which, symptoms of the disease might not be shown before two weeks of the infection. The World Health Organization WHO recognized the spread of COVID-19 as a pandemic on March 11th, 2020. In the first period of the virus's spread, specifically in January and February of 2020, Italy, Iran, South Korea, Japan, and China reported increasing numbers of cases. Later that month, specifically on the 26th of February, the number of cases outside China rapidly exceeded the number of cases inside China, with the total number of cases reaching 2,790 distributed in 37 countries. During the next few days, the virus spread around the world at a steady speed, and there was no way or method to find a solution or treatment for its spread. COVID-19 had devastating effects on all living areas and on all industries, in which, it had shocking effects and frightening figures related to the movement of the global economy and companies in a manner related to the repetition and duration of closures in addition to effects beyond description related to current and future effects in connection with the methodology of higher education, universities, and educational institutions, and the related future repercussions. COVID-19 causes many symptoms such as fever, dry cough, fatigue, headache, loss of the sense of smell and taste, it also causes difficulty breathing and nasal congestion. COVID-19 is an abbreviation for coronavirus disease of 2019. Throught out this paper, The virus is mentioned as Coronavirus, COVID, and COVID-19.